2019
DOI: 10.4081/mrm.2018.122
|View full text |Cite
|
Sign up to set email alerts
|

Non-typeable Haemophilus Influenzae detection in the lower airways of patients with lung cancer and chronic obstructive pulmonary disease

Abstract: Background: Chronic airway inflammation and hypersensitivity to bacterial infection may contribute to lung cancer pathogenesis. Previous studies have demonstrated that nontypeable Haemophilus influenzae (NTHi) is the most common colonizing bacteria in the lower airways of patients with COPD. The objective of this study was to determine the presence of NTHi and immunoglobulin concentrations in patients with lung cancer, COPD and controls. Methods: Serum and bronchial wash samples were collected from patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Jungnickel et al indicated that the epithelial cytokine IL-17C mediates the tumor-promoting effect of bacteria, such as NTHi, through neutrophilic inflammation (123). Recently, growing awareness of the importance of NTHi in the pathophysiology of COPD has been observed, and COPD-like airway inflammation induced by NTHi provides a tumor microenvironment that favors lung tumor promotion and progression (124)(125)(126). Thus, NTHi may act as a bridge between COPD and lung cancer.…”
Section: Inflammatory Pathways and Immune Responsementioning
confidence: 99%
“…Jungnickel et al indicated that the epithelial cytokine IL-17C mediates the tumor-promoting effect of bacteria, such as NTHi, through neutrophilic inflammation (123). Recently, growing awareness of the importance of NTHi in the pathophysiology of COPD has been observed, and COPD-like airway inflammation induced by NTHi provides a tumor microenvironment that favors lung tumor promotion and progression (124)(125)(126). Thus, NTHi may act as a bridge between COPD and lung cancer.…”
Section: Inflammatory Pathways and Immune Responsementioning
confidence: 99%